Preparation and Characterization of New Tetra-Dentate N2O2 Schiff Base with Some of Metal Ions Complexes - Naser Shaalan; Waleed Madhloom Khalaf; Shatha Mahdi (Universitas Gadjah Mada, 2022)
This study describes preparation a new series of tetra-dentate N2O2 dinuclear complexes Cr(III), Co(II)and Cu(II) of the Schiff base 2-[5-(2-hydroxy-phenyl)-1,3,4-thiadiazol-2-ylimino]-methyl-naphthalen-1-ol], (LH2) derived from 1-hydroxy-naphthalene-2-carbaldehyde with 2-amino-5-(2-hydroxy-phenyl)-1,3,4-thiadiazole. These ligands were characterized by FT-IR, UV-Vis, Mass spectra, elemental analysis, and 1H-NMR. All prepared complexes have been characterized by conductance measurement, magnetic susceptibility, electronic spectra, infrared spectrum, thermal Analysis (TGA), and metal analysis by atomic absorption. The stoichiometry of metal to ligand, magnetic susceptibility, and electronic spectra measurements show an octahedral geometry for all (Cr3+, Co2+, Cu2+) complexes. Conductivity measurement shows that the prepared (Co2+, Cu2+) complexes were nonelectrolyte except (Cr3+). Studying the extraction efficiency such as ligand concentration, temperature and incubation time, centrifuge time, amount of surfactant were evaluated and optimized. The linear range of ions Cr(III), Co(II) and Cu(II) with ligand (0.2–3, 0.2–4, 0.2–3, µg mL–1), each individually, and relative standard deviation (0.15%, 0.34%, 0.46%). The successful method was applied for the determination of trace metal ions in the wastewater.